Pengaruh Kepemimpinan Transformasional Terhadap Berbagi Pengetahuan Tacit Dan Eksplisit Dengan Efikasi Diri Sebagai Variabel Pemoderasi - Kurniati, Panca; Fithrayudi Triatmaja, Muh; Arifiyanto, Muh (Neraca, 2024)
This study explores the impact of transformational leadership on tacit and explicit knowledge sharing, with self-efficacy as a moderating variable. Data were collected through questionnaires distributed to employees of private companies and civil servants (PNS) in Pekalongan City using Google Forms. The analysis method employed was Structural Equation Modeling (SEM) using SmartPLS 3.0 software. The results indicate that transformational leadership has a positive and significant effect on both tacit and explicit knowledge sharing. However, self-efficacy does not moderate the relationship between transformational leadership and tacit knowledge sharing. Conversely, self-efficacy significantly moderates the relationship between transformational leadership and explicit knowledge sharing. These findings provide new insights for leadership theory and practice, as well as knowledge management within organizations, particularly in enhancing the effectiveness of knowledge sharing through transformational leadership. REFERENSI Alavi, M. & Leidner, D. E. 2001. Review: Knowledge Management and Knowledge Management Systems: Conceptual Fondations and Research Issues. MIS Quarterly, 25(1):107-136. Bartol, K. M. & Srivastava, A. 2002. Encouraging Knowledge Sharing: The Role Of Organizational Rewards Systems. Journal of Leadership and Organization Studies, 9(1):64-76. Bechina, A. A. & Bommen, T. 2006. Knowledge Sharing Practices: Analysis Of A Global Scandinavian Consulting Company. The Electronic Journal Of Knowledge Management, 4(2):109-116. Berman, S. L., Down, J. & Hill, C. W. 2002. Tacit knowledge as a Source of Competitive Advantage in the National Basketball Association. Academy of Management Journal, 45(1):13-31. Bock, G.W. & Kim. Y.G. 2002. Breaking the Myths of Rewards: An Exploratory Study of Attitudes About Knowledge Sharing. Information Resources Management Journal, 15(2):14-21. Gudono. 2011. ”Analisis Data Multivariat Ed.1”. BPFE: Yogyakarta. Gudono. 2012. ”Analisis Data Multivariat Ed.2”. BPFE: Yogyakarta. Hair, J. F., Black, W. C., Babin, B. J. & Anderson, R. E. 2010. Multivariate Data Analysis. New Jersey: Pearson Prentice Hall. Hakami, Y., Tam, S., Bursalim, A. H. & Husin, A. R. C. 2014. A Review of Faktors Affecting The Sharing of Knowledge in Social Media. Science International, 26(2):679-688. Hansen, M. T., Mors, M. L. & Lova’s, B. 2005. Knowledge sharing in organizations: Multiple networks, multiple phases. Academy of Management Journal, 48(5):776-793. Hair, J. F., Black, W. C., Babin, B. J. & Anderson, R. E. 2010. Multivariate Data Analysis. New Jersey: Pearson Prentice Hall. Hakami, Y., Tam, S., Bursalim, A. H. & Husin, A. R. C. 2014. A Review of Faktors Affecting The Sharing of Knowledge in Social Media. Science International, 26(2):679-688. Hartono, J. 2011. Pedoman Survei Kuesioner. BPFE: Yogyakarta. Hartono, J. 2016. Metode Penelitian Bisnis. Salah Kaprah dan Pengalaman-pengalaman. Edisi 6. BPFE: Yogyakarta. Hansen, M. T., Mors, M. L. & Lova’s, B. 2005. Knowledge sharing in organizations: Multiple networks, multiple phases. Academy of Management Journal, 48(5):776-793. Hsu,C. & Lin, J. C. 2008. Acceptance of Blog Usage: The Role of Technology acceptance, Social influence and Knowledge Sharing Motivation. Information & Management, 45:65-74. Husman, M. & Wulf, V. 2005, The Role Of Information Technology In Building And Sustaining The Relational Base Of Communities. The Information Society, 21(2):81-89. Imam Ghozali. 2018. Aplikasi Analisis Multivariate dengan Program IBM SPSS 25 (edisi 9), Semarang: Badan Penerbit Universitas Diponegoro. Ipe, M. 2003. Knowledge Sharing in Organizations: A Conceptual Framework”. Human Resource Development Review, 2:337-359. Mital, M., Israel, D. & Agarwal, S. 2010. Information Exchange and Information Disclosure and In Social Networking Web Sites. The Learning Organization, 17(6):479-489. Neuman, W. L. 2006. Basics of Social Research: Qualitative and Quantitative Approaches. USA : Pearson International Edition. Nonaka, I. & Takeuchi, H. 1995. The Knowledge-Creating Company: How Japanese Companies Create the Dynamics of Innovation. New York: Oxford University Press. Nonaka, I. & Konno, N. 1998. The Concept of ‘Ba’: Bilding A Foundation for Knowledge Creation. California Management Review, 40(3):40-53. Wahana Komputer. 2017. Ragam Model Penelitian & Pengolahannya dengan SPSS, Semarang: Penerbit ANDI. Ruggles, R. 1998. The State Of Notion: Knowledge Management In Practice. California Management Review, 40:80-89. Roblek, V., Pejic Bach, M., Mesko, M. & Bertoncelj, A. 2013. The Impact Of Social Media To Value Added In Knowledge-based Industries. Kybernetes, 42(4):554-568. Ryu, S., Ho, S. H., & Han, I. 2003. Knowledge Sharing Behavior Of Physicians In Hospitals. Expert Systems with Applications, 25(1):113−122. Scheepers, H., Scheepers, R., Stockdale, R. & Nurdin, N. 2014. The Dependent Variable in Social Media Use. Journal of Computer Information Systems, 54(2):25-34. Sekaran, U. 2017. Metode Penelitian Untuk Bisnis 1 (edisi 6), Jakarta: Salemba Empat. Sekaran, U. 2017. Metode Penelitian Untuk Bisnis 2 (edisi 6), Jakarta: Salemba Empat. Sondergaard, S., Kerr, M. & Clegg, C. 2007. Sharing Knowledge: Contextualising Socio-Technical Thinking And Practice. The Learning Organization, 14(5):423−435. Sun, Y., Lim, K. H., Peng, Z. & Wang, W. M. 2014. Norm of Reciprocity, Reciprocal Benefits, and Reciprocal Relationships: A Revisit of the Role of Reciprocity in Knowledge Sharing. Thirty Fifth International Conference on Information Systems, pp:1-16. Suliyanto. 2011. Ekonometrika Terapan: Teori & Aplikasi dengan SPSS. Yogyakarta: Penerbit ANDI. Zheng, Y., Li, L. & Zheng, F. 2010. Social Media Supportfor Knowledge Management. International Conference on Management and Service Science (MASS), WuHan, 2010.